(untitled) (Research, Society and Development, 2021)
Objective: to reflect on how the sequelae of Covid-19 can impact workers’ health. Methods: This is a reflection. The selected articles were organized according to the thematic axes: Sequelae of Covid-19 and Impacts on workers’ health. Results: Covid-19 is a disease with aspects yet to be revealed, one of which is the consequences on the health of the population. This condition is worrisome, given the risk of overloading health systems. The complications of Covid-19 are capable and capable of interfering with the worker’s health, whether through difficulties in occupational exercise or even because they cause early retirement. It is believed that some sequelae are treatable, however, they can be lost for some time, in other cases, there may be irreversible sequelae. Conclusion: It is necessary to establish public health, social security and labor policies that guarantee workers adequate health treatment, job stability and social benefits.